THE MAIN FACTORS AFFECTING POULTRY PRODUCTION IN LIBYA - Grepay, Nassar (Acta Scientiarum Polonorum. Oeconomia, 2009)
The aim of the paper is to analyze and present some selected issues of poultry production in Libya. There were presented technological as well as economic factors that cause poultry production is very important. Poultry production in Libya is conditioned by feeding process, selection of chicks and veterinary health care. Feeding process is a very important factor upon which production efficiency depends. It infl uences not only the quantity of poultry production but also the quality of it. Poultry breeding process depends on the quality of veterinary health care for chicks (breading material) and feed processing.